PROSES PEMBELAJARAN BIOLOGI DALAM PELAKSANAAN KURIKULUM MERDEKA DI SMAN 7 TANGERANG - Yayu widiya (Jurnal Inovasi Pendidikan dan Sains, 2022)
The curriculum is a guideline in the implementation of education in schools, an independent curriculum is made to make it easier for teachers and students to carry out the learning process in schools based on the principle of independent learning, where teachers and students have freedom in designing learning. This research was conducted to find out how the learning process is using a curriculum that covers approaches, models, achievement methods, learning objectives, processes and evaluations of biology learning at SMAN 7 Tangerang. Based on the results of research, the independent curriculum is applied to class X students who include intracurricular learning and projects to strengthen the profile of pancasila (5P) students, the scientific learning approach as well as the use of the models and methods determined by teachers and the selection of specialization subjects. The learning assessment is carried out with 2 report cards that are distinguished from knowledge assessment and project assessment. The shortcomings in the use of an independent curriculum are the lack of facilities in the form of sufficient learning spaces, as well as giving complicated work to school administrative staff in their management. In addition, the application of an independent curriculum in biology learning can make students determine interests, talents and also freedom in the learning process so that students can explore more Keywords : Learning, Biology, Independent Curriculum